Graphs for Pattern Recognition. Infeasible Systems of Linear Inequalities - Gainanov, Damir (De Gruyter, 2016)
Data mining and pattern recognition are areas based on the mathematical constructions discussed in this monograph. By using combinatorial and graph theoretical techniques, it is shown how to tackle infeasible systems of linear inequalities. These are, in turn, building blocks of geometric decision rules for pattern recognition.